Maori Models of Mental Wellness - McNeill, Hinematau (Te Kaharoa, 2009)
This article outlines the development a model of mental wellness – Te Ao Tūtahi – that encompassed the complexity of Maori existence was initiated by the Māori forensic psychiatrist, Rees Tapsell. The objective of the proposed model was to depict the different cultural influences and experiences that have shaped Maori contemporary lifeways. The model was shaped by research into Tūhoe Kaumātua Mental Wellness undertaken in 2002 and was designed can be best described as an ontological model of mental wellness.